Achieving sustainable medical tourism: unpacking privacy concerns through a tripartite game theoretic lens - Wang, Ran; Geng, Songtao (Frontiers in Public Health, 2024)
Introduction Medical tourism has grown significantly, raising critical concerns about the privacy of medical tourists. This study investigates privacy issues in medical tourism from a game theoretic perspective, focusing on how stakeholders’ strategies impact privacy protection. Methods We employed an evolutionary game model to explore the interactions between medical institutions, medical tourists, and government departments. The model identifies stable strategies that stakeholders may adopt to protect the privacy of medical tourists. Results Two primary stable strategies were identified, with E6(1,0,1) emerging as the optimal strategy. This strategy involves active protection measures by medical institutions, the decision by tourists to forgo accountability, and strict supervision by government departments. The evolution of the system’s strategy is significantly influenced by the government’s penalty intensity, subsidies, incentives, and the compensatory measures of medical institutions. Discussion The findings suggest that medical institutions are quick to make decisions favoring privacy protection, while medical tourists tend to follow learning and conformity. Government strategy remains consistent, with increased subsidies and penalties encouraging medical institutions towards proactive privacy protection strategies. We recommend policies to enhance privacy protection in medical tourism, contributing to the industry’s sustainable growth.